2022
DOI: 10.3389/fpubh.2022.995382
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination hesitancy and willingness among pregnant women in Italy

Abstract: BackgroundPregnant women, especially those with comorbidities, compared to those non-pregnant, have higher risk of developing a severe form of COVID-19. However, COVID-19 vaccine uptake is very low among them.MethodsAn anonymous questionnaire was administered to randomly selected women 18 years of age that were currently pregnant or had just given birth between September 2021 and May 2022 in the geographic area of Naples. Vaccine hesitancy was assessed using the vaccine hesitancy scale (VHS).ResultsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 47 publications
8
51
1
Order By: Relevance
“…These finding are unexpected and disappointing as the severity of COVID-19 is well proven [ 1 , 2 , 3 , 4 ] and there is a large amount of data supporting the benefits and safety of this vaccination [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, similar concerns have been reported in other studies among pregnant women [ 14 , 34 , 35 , 36 , 40 ] and midwives [ 41 ]. Thus, the COVID-19 vaccination coverage among pregnant women may be enhanced by education interventions targeted to midwives to improve their awareness of the clinical burden of the disease and to address their concerns about this vaccination.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These finding are unexpected and disappointing as the severity of COVID-19 is well proven [ 1 , 2 , 3 , 4 ] and there is a large amount of data supporting the benefits and safety of this vaccination [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, similar concerns have been reported in other studies among pregnant women [ 14 , 34 , 35 , 36 , 40 ] and midwives [ 41 ]. Thus, the COVID-19 vaccination coverage among pregnant women may be enhanced by education interventions targeted to midwives to improve their awareness of the clinical burden of the disease and to address their concerns about this vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, midwives with more years of activity and those who have never provided assistance to a pregnant infected by SARS-CoV-2 had a positive influence in providing information regarding the vaccination. This last result is unexpected, as studies among other groups found that those who knew someone infected were more willing to receive the COVID-19 vaccination [ 14 , 26 , 42 ]. Furthermore, midwives who considered the COVID-19 vaccination useful for pregnant women were more likely to always recommend it.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All data were collected through a self-administered questionnaire adopted and modified from previously published studies of the research group (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The questionnaire required 5-10 min to complete and capture the following information: a) sociodemographic, general, and professional characteristics (14 questions), including gender, age, relationship status, degree of education, professional role, duration of employment in the healthcare profession, area of working activity, self-rated health status, and previous COVID-19 infection; b) source(s) from which they receive information related to the second booster dose and whether they would like to get additional information (2 questions); and c) attitudes and behaviors (7 questions).…”
Section: Survey Developmentmentioning
confidence: 99%